(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
In present study the new series of 3-(Aryl)-5-[4-(2, 4-Dichlorophenylmethoxy)-3-methoxyphenyl]-4, 5-dihydro pyrazoline (2a-k) and 3-(Aryl)-5-[4-(2, 4-Dichlorophenylmethoxy)-3-methoxyphenyl]-4, 5-dihydroacetyl pyrazoline (3a-k) derivatives were synthesized from various substituted 3-Methoxy-4-(2, 4-Dichlorophenyl methoxy) chalcones (1a-k). The new chalcones were synthesized using various acetophenones with newly synthesized aldehyde of vanillin analog by Claisen-Schmidt condensation. Characterization of pyrazoline derivatives have been established on the basis of IR, NMR, Mass and elemental analyses. The derivatives were screened for their in vitro antimicrobial Screening.